General practitioners knowledge and management of whiplash associated disorders and post-traumatic stress disorder: Implications for patient care - Brijnath, Bianca; Bunzli, S.; Xia, T.; Singh, N.; Schattner, P.; Collie, A.; Sterling, M.; Mazza, D. (BioMed Central Ltd., 2016)
© 2016 The Author(s). Background: In Australia, general practitioners (GPs) see around two-thirds of people injured in road traffic crashes. Road traffic crash injuries are commonly associated with diverse physical and psychological symptoms that may be difficult to diagnose and manage. Clinical guidelines have been developed to assist in delivering quality, consistent care, however the extent to which GPs knowledge and practice in diagnosing and managing road traffic crash injuries concords with the guidelines is unknown. This study aimed to explore Australian GPs knowledge, attitudes and practices regarding the diagnosis and management of road traffic crash injuries, specifically whiplash associated disorders (WAD) and post-traumatic stress disorder (PTSD). Method: A cross-sectional survey of 423 GPs across Australia conducted between July and December 2014. We developed a questionnaire to assess their knowledge of WAD and PTSD, confidence in diagnosing and managing WAD and PTSD, frequency of referral to health providers, barriers to referral, and attitudes towards further education and training. Factor analysis, Spearman's correlation, and multiple ordered logistic regressions were performed. Results: Overall, GPs have good level knowledge of WAD and PTSD; only 9.6 % (95 % CI: 7.1 %, 12.8 %) and 23.9 % (95 % CI: 20.8 %, 28.2 %) of them were deemed to have lower level knowledge of WAD and PTSD respectively. Key knowledge gaps included imaging indicators for WAD and indicators for psychological referral for PTSD. GPs who were male, with more years of experience, working in the urban area and with higher knowledge level of WAD were more confident in diagnosing and managing WAD. Only GPs PTSD knowledge level predicted confidence in diagnosing and managing PTSD. GPs most commonly referred to physiotherapists and least commonly to vocational rehabilitation providers. Barriers to referral included out-of-pocket costs incurred by patients and long waiting times. Most GPs felt positive towards further education on road traffic crash injury management. Conclusion: This study has enhanced understanding of the knowledge skills and attitudes of GPs towards road traffic crash injury care in Australia, and has identified areas for further education and training. If delivered, this training has the potential to reduce unnecessary imaging for WAD and optimise the early referral of patients at risk of delayed recovery following a road traffic crash.